A casa da UMMAH: comunidades religiosas islâmicas sunitas no Nordeste do Brasil – Paraíba e Agreste de Pernambuco - Lima, Vanessa Karla Mota de Souza (2016)
To investigate, the Sunni Islamic communities in Paraíba and Pernambuco wild through anthropological contributions, as Muslim identities and how these reverse individuals perceive themselves as participants of transnational Islamic community, the ummah are built. Through participant observation and discourse analysis of supporters of the Islamic religion, to understand how is this religious experience of "being Muslim" in northeastern Brazil. Understanding from Islamic theological categories of Tawhid / Taweed and reversal modes of assimilation and sharing of practices of transnational faith community, networks and flows of these communities in their transits of faith and your new settings from the Brazilian context by these individuals. the search field raids were carried out in the cities of João Pessoa (PB), Caruaru (PE) and Canhotinho (PE) in the search for discourse and practices of Muslims. It understood that the assimilation of religion and their experience as members of the Islamic faith community are given through the construction of a religious identity and doctrinal identification with regard to ritual practices and experiences shared in sacralized spaces and society.